A Study on the Prediction of Reproductive Outcomes in Frozen Embryo Transfer Cycles by Calculating the Volume of Uterine Junctional Zone with Three-Dimensional Ultrasound - Liu, Yan; Wang, Lei; Wang, MeiXian; Jiang, Yu; Xia, TingTing; Yue, QingXiong; Sha, YuJia; Huang, Ying (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To prospectively study the inﬂuence of the volume of the uterine junctional zone (JZ) as a novel predictor of reproductive outcomes in frozen embryo transfer cycles.Methods Among the first 30 patients, intra- and interobserver repeatability was evaluated and expressed as a coefficient of repeatability. The same classification system was used to evaluate the JZ of 142 infertility patients undergoing in vitro fertilization (IVF). Ultrasonography was performed on the day before transplantation. The three-dimensional (3D) volume images were then analyzed to obtain the volume of the endometrium (EV), the average thickness of the JZ on the coronal plane, and the volume of the JZ (JZV). The JZV was then divided by the EV. These parameters were compared with the outcomes of clinical pregnancy.Results The 3D image showed that the JZ achieved a good intra- and interobserver consistency (k = 0.862, k = 0.694). The total pregnancy rate was 47%. There was a highly significant difference between pregnant and non-pregnant women with respect to age (p < 0.001), JZV (p = 0.003), and JZV/EV (p < 0.001) on the day before transplantation. Age and JZV/EV were independent factors for predicting the success of IVF transplantation (p = 0.010, p = 0.016). The area under the ROC curve of JZV/EV in predicting clinical pregnancy was 0.688, the cut-off value was 0.54, the sensitivity was 83.8%, and the specificity was 50.0%.Conclusion Age and JZV/EV are independent factors for predicting the success of frozen embryo transfer cycles in IVF. A smaller JZV/EV was more beneficial for clinical pregnancy.
Keywords: three-dimensional ultrasound; endometrial volume; in vitro fertilization; clinical pregnancy; uterine junctional zone